PERENCANAAN PEMBANGUNAN MODEL AGREGAT TERHADAP PERTUMBUHAN EKONOMI - Dina Eva Santi Silalahi (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2020)
Development planning (aggregate model) is a very important component prepared before the development activities are carried out. The plan is part of the Medan City strategic plan (Renstra) which was prepared in advance from the National Medium-Term Development Plan (RPJMN). The planning is expected to provide results that are right on target and in accordance with the targets to be achieved in supporting the economy in the city of Medan. This study aims to analyze the effect of development planning (aggregate models) namely government spending and investment on the economic growth of the city of Medan during the period 2008-201 obtained from the Central Statistic Agency of Medan in 2007 to 2018.. This research is quantitative by using time-series data for 10 years and the data analysis technique used is Multiple Linear Regression. The results showed that government spending did not affect the economic growth of the city of Medan, while investment affected the economic growth of the city of Medan. Every 1% increase in investment will increase 0.659% economic growth in the city of Medan (ceteris paribus). Taken together, government spending and investment influence the economic growth of the city of Medan at a significance level of 5%.